Upaya Pembentukan Karakter Peserta Didik melalui Pembiasaan Salat Dhuha di SDIT Insan Mulia Bojong Kulur Kab. Bogor - Dzikro, Fattaliyati (Jurnal Inovasi Pembelajaran di Sekolah, 2025)
The actualization of Islamic character values in Islamic education needs to be seen as an important issue in efforts to cultivate Islamic ideology as a way of life. However, efforts to actualize Islamic moral values require a long process, so that the cultivation is not just a formality but has entered the practical realm. This is needed to overcome the moral decadence of the increasing number of students. There are many cases of student misbehavior, one thing that can be done is to get students used to praying the Duha prayer, because getting used to the Duha prayer can improve the discipline character, religious character of students, the character of responsibility for students, the character of an independent attitude. This research is qualitative field research that uses a phenomenological approach with sources from school principals, teachers, vice principals and students at SDIT Insan Mulia Salah and books, journals and articles that are relevant to this research. Data collection was carried out by observation, interviews or interviews and documentation, after the data is collected it is then analyzed in stages data collection, reduction, display, and drawing conclusions/verification. Research results: Efforts to shape students' character through the habit of Duha prayers at SDIT Insan Mulia Bojong Kulur District. Bogor is done before starting learning, this is done istiqomah, this habituation is to stimulate or get students used to starting activities with good things. This good habit becomes part of students' morals towards Allah SWT. Students can become servants who are always grateful for all the blessings they receive and use their time to always do good without wasting it. The habit of Duha prayer can improve the character of discipline, the religious character of students, the character of responsibility for students, the character of an independent attitude, and through the habit of Duha prayer can improve the character of honesty which in the end students will have good morals